Experimental analysis of brick masonry veneers walls under out-of-plane loading - Martins, Andreia (2020)
The evaluation of seismic vulnerability of existing buildings with masonry veneer systems has been recog-nized as a major problem because of the large number of buildings constructed before the development of rational seismic codes. This resulted in the construction of masonry veneers without reference to the design to seismic action and adequate constructive detailing. In order to contribute to increasing of knowledge about seismic behaviour of brick veneer walls, an experimental campaign was developed on testing quasi-statically full-scale systems under in-plane and out-of-plane loading. This paper describes in detail the out-of-plane performance of a constructive system characteristic of Portugal and South of Europe, constituted of brick masonry veneer leaf connected to an infill wall inserted in a reinforced concrete (rc) frame. A descrip-tion of the test setup for the out-of-plane tests is provided and the main results, including the damage pat-terns and force displacement diagrams, are presented and discussed.